Izafet Constructions in the Monument "Gulistan Bit Turki" (Syntactic and Semantic Analysis) - Zinedina А.С.; Eskindirova М.Ж.; Yespekova Л. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2024)
This article analyzes the semantics of izafet constructions in the "Gulistan bit Turki" monument. The research focuses on studying the syntactic structures of Turkic written monuments, particularly izafet constructions, to gain a deeper understanding of the semantic aspects of the syntactic system of Turkic languages of that period. Izafet constructions help determine the semantic connections between objects, phenomena, and concepts in the language, thus playing a significant role in Turkic linguistics. The aim of the study is to identify the semantic features of izafet relations in the "Gulistan bit Turki" text and analyze their grammatical and semantic connections. By distinguishing the types of izafet constructions (I, II, III), the study examines the use of possessive, subordinate, and metaphorical meanings and their semantic roles in the written monument. Structural-semantic, historical-comparative, contextual, and syntactic analysis methods are employed in this research. These methods allow for an examination of the semantic aspects of izafet constructions in the text. The semantic analysis of izafet constructions helps explain the fundamental principles of the syntactic system of Turkic languages and reveals the linguistic value of this monument. The research findings can be applied in linguistics, literary studies, and cultural studies. The study offers a comprehensive analysis of the semantics of izafet relations in "Gulistan bit Turki" and demonstrates their importance in shaping the semantic system of Turkic languages. This research makes a significant contribution to the deeper understanding of the historical aspects of the syntactic structure of Turkic languages.